A comparison between alkali‐activated slag/fly ash binders prepared with natural seawater and deionized water. Issue 9 (1st May 2022) - Ren, Jie; Sun, Hongfang; Li, Qun; Li, Zhenming; Zhang, Xiaogang; Wang, Yanshuai; Li, Linfei; Xing, Feng
Abstract: In this research, the effects of natural seawater (SW) on the properties of alkali‐activated slag/fly ash (AASF) are studied. AASF prepared with deionized water is set as the reference mixture. The results showed that the use of natural SW resulted in a prolonged setting time and lower heat release, but no obvious impact on the flowability of AASF specimens. The long‐term compressive strength became higher when SW was used, whereas the corresponding flexural strength and fractural toughness turned lower. The use of SW induced the formation of new products that were not identified in the reference mixture, such as Cl–hydrocalumite and gypsum. In addition, it is evidenced that the dissolution of fly ash (FA) particles was significantly delayed with the incorporation of SW. All these results were related to the various ions introduced by the natural SW and their interactions with the alkaline activator as well as the precipitation of salts on slag and FA surfaces or in the matrix.